Eggerthella lenta DSM 2243 Alleviates Bile Acid Stress Response in Clostridium ramosum and Anaerostipes caccae by Transformation of Bile Acids - Pedersen, Kristian Jensen; Haange, Sven-Bastiaan; Žížalová, Kateřina; Viehof, Alina; Clavel, Thomas; Leniček, Martin; Engelmann, Beatrice; Wick, Lukas Y; Schaap, Frank G; Jehmlich, Nico; Rolle-Kampczyk, Ulrike; von Bergen, Martin (Microorganisms, 2022)
Bile acids are crucial for the uptake of dietary lipids and can shape the gut-microbiome composition. This latter function is associated with the toxicity of bile acids and can be modulated by bile acid modifying bacteria such as Eggerthella lenta, but the molecular details of the interaction of bacteria depending on bile acid modifications are not well understood. In order to unravel the molecular response to bile acids and their metabolites, we cultivated eight strains from a human intestinal microbiome model alone and in co-culture with Eggerthella lenta in the presence of cholic acid (CA) and deoxycholic acid (DCA). We observed growth inhibition of particularly gram-positive strains such as Clostridium ramosum and the gram-variable Anaerostipes cacae by CA and DCA stress. C. ramosum was alleviated through co-culturing with Eggerthella lenta. We approached effects on the membrane by zeta potential and genotoxic and metabolic effects by (meta)proteomic and metabolomic analyses. Co-culturing with Eggerthella lenta decreased both CA and DCA by the formation of oxidized and epimerized bile acids. Eggerthella lenta also produces microbial bile salt conjugates in a co-cultured species-specific manner. This study highlights how the interaction with other bacteria can influence the functionality of bacteria.
Keywords: metabolomics; bile acids; eggerthella lenta; hydroysteroid dehydrogenase; gut microbiome interaction; metaproteomics